KAJIAN KUAT TEKAN BETON FC’30 DENGAN BAHAN TAMBAH GEOGRID - Kalsum, Fhelvia Umi; Rosyad, Farlin (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Technological advances and the economic crisis that occurred in Indonesia, directed infrastructure development towards the use of Structures with lightweight materials. But overall it does not have an impact on increasing the Strength of the Structure. The use of lightweight materials as a structural material will reduce the total weight of a building, thereby reducing the supporting parts and foundations. Concrete is a material commonly used for Structures. This is because Concrete has many advantages when compared to other building materials. However, concrete has one weakness, namely its density is quite high so that the dead load on a structure becomes large. Based on SNI (03-2847-2002), concrete is a mixture of Portland cement or other hydraulic cement, fine aggregate, coarse aggregate, and water with or without additives to form a solid mass. There are various types of additives used in concrete mixtures, namely steel. Polymer (polyoropylene), glass, and carbon..Keywords: Geogrid concrete compressive strength